Le polar après la révolution. À propos d’un nouvel ouvrage sur le roman policier (Marcela Poučova. Sous les pavés, le noir! Le roman noir dans la France post-68. Brno: Masarykova univerzita, 2017. 206 p. ISBN 978-80-210-8846-7) - Kirill A. Chekalov (Studia Litterarum)
In her new book, a Czech researcher Marcela Pouchova describes the evolution of the French detective novel after the revolutionary events of 1968. The main focus of the book is on the reflection of the socio-political realities of this time in the works of the masters of this genre. Analyzing the work of such writers as J.-P. Mansel (who was also a genre theoretician, and first proposed the term “neopolar”), J. Amila, D. Genex, J.-CL. Izzo, J.-B. Pu, and P. Raynal – in total, about sixty novels – Pocova examines this vast production in the tradition of popular literature and briefly describes the literature of the polar. M. Pouchova mainly bears on the sociological approach to literature (she appeals to the methodology of P. Bourdieu and the Frankfurt school), which does not prevent her from analyzing the narrative features of the texts under consideration, including the use of literary clichés. Regrettably, the author has paid little attention to the film adaptations of the detective novels (in some cases, they have earned greater fame than texts), as well as to use of ergotism.